(untitled) (Journal of the College of Basic Education, 2022)
The glutathione S-transferases (GSTs) are involved in the metabolism of many xenobiotics, including an array of environmental carcinogens, pollutants, and drugs. GSTs play an important role in cellular protection against oxidative stress. Genetic polymorphisms in these genes may lead to interindividual variation in susceptibility to various diseases such as diabetes mellitus type2. A relationship between these polymorphisms and changes in the clinical parameters of diabetic patients has also been investigated. However, the results diverge considerably among the studies, Thus, this case-control study was designed to contribute to existing knowledge, as there are no studies on this issue performed in the Iraqi population. The study consisted of 50 clinically diagnosed diabetes mellitus type2 patients and 31 healthy control men. Analyses of GST polymorphism were carried out by multiplex PCR. Our results showed GSTT1 null and for GSTM1 null compared to GSTT1 present and GSTM1 present genotypes respectively the proportion of GSTT1 null genotypes were higher in diabetic patients as compared to controls (30 % versus 6.5%). No significant difference of the frequency of GSTM1 null that observed between cases and controls (52% versus 54.8%). We conclude GSTT1 gene polymorphisms may play an important role in diabetes mellitus type 2 pathogenesis. The GSTM1-null genotype may be helpful in identifying individuals at high risk for essential hypertension in study population and the potential role of GSTM1 polymorphism as a marker of susceptibility to type 2 diabetes mellitus needs further studies in a larger number of patients. GSTT1 and GSTM1 genotypes do not have an effect on blood lipids given exposure to diabetes mellitus.